2014
DOI: 10.1080/10402004.2014.951751
|View full text |Cite
|
Sign up to set email alerts
|

A More General Capillary Adhesion Model Including Shape Index: Single-Asperity and Multi-Asperity Cases

Abstract: The capillary interaction between a sphere and a flat substrate has been widely investigated. Considering the complex shape of single asperities in real configurations, a more general model of capillary adhesion force including a power law shape index of asperities is developed. For the interaction between a single asperity with any axisymmetric power law shape profile and a flat substrate, the deformation originating from the adhesive force and the contact force is included in the model. Combining the single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…Based on the existing models, , the meniscus surface parallel to the symmetry axis is a circular arc of radius r between two identical spheres with radius R s . Figure shows the two principal radii l and r of the capillary with R s ≫ l ≫ r .…”
Section: Data Analysesmentioning
confidence: 99%
“…Based on the existing models, , the meniscus surface parallel to the symmetry axis is a circular arc of radius r between two identical spheres with radius R s . Figure shows the two principal radii l and r of the capillary with R s ≫ l ≫ r .…”
Section: Data Analysesmentioning
confidence: 99%
“…22,23 Wang, et al found that a more detailed description of rough surfaces was helpful to better quantify the capillary adhesion between rough surfaces. 24 Takao, et al analyzed the adhesive contact problem for anisotropic materials by considering surface stress and surface elasticity. 25 Fan, et al established a cohesive zone model of adhesive contact in nonhomogeneous materials.…”
Section: Introductionmentioning
confidence: 99%
“…Wang and Regnier developed a capillary adhesion model for the contact of a single asperity of a power law shape with a flat surface and extended it to the contact between rough surfaces [38].…”
Section: Introductionmentioning
confidence: 99%